Discrete element modeling of cemented sand and particle crushing at high pressures - de Bono, John Patrick (2013)
This project aims to provide an insight into the behaviour of cemented sand under high pressures, and to further the understanding of the role of particle crushing. The discrete element method is used to investigate the micro mechanics of sand and cemented sand in high-pressure triaxial tests and one-dimensional normal compression.